2021
DOI: 10.1055/s-0041-1725155
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 Disease on Urology Practice

Abstract: The diagnosis and timely treatment of cancer patients should not be compromised during an infectious disease pandemic. The pandemic of coronavirus disease 2019 (COVID-19) has serious implications on urology practice and raises particular questions for urologists about the management of different conditions. It was recommended to cancel most of the elective urological surgeries. Urological cancers surgeries that should be prioritized are radical cystectomy for selective tumors, orchiectomy for suspected testicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Although the optimal duration of maintenance therapy for patients with high-risk NMIBC remains controversial, EAU’s guidelines recommend 3-week instillations at 3, 6, 12, 18, 24, 30, and 36 months. As the COVID-19 pandemic has had a serious impact on urological treatments [ 9 ], Lenfant et al reported that intravesical BCG therapy could be discontinued safely for patients with high-risk NMIBC [ 8 ]. Furthermore, according to EAU’s NMIBC panel during the pandemic, a 1-year BCG maintenance immunotherapy in patients with high-risk NMIBC was recommended [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the optimal duration of maintenance therapy for patients with high-risk NMIBC remains controversial, EAU’s guidelines recommend 3-week instillations at 3, 6, 12, 18, 24, 30, and 36 months. As the COVID-19 pandemic has had a serious impact on urological treatments [ 9 ], Lenfant et al reported that intravesical BCG therapy could be discontinued safely for patients with high-risk NMIBC [ 8 ]. Furthermore, according to EAU’s NMIBC panel during the pandemic, a 1-year BCG maintenance immunotherapy in patients with high-risk NMIBC was recommended [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The coronavirus disease 2019, also known as COVID-19, has spread around the world, and the World Health Organization officially declared it a pandemic on March 11, 2020. Healthcare has been severely impacted, and urology practices have also been affected by the COVID-19 pandemic [ 9 ]. According to EAU’s COVID-19 recommendations, EAU’s NMIBC panel recommends 1-year intravesical BCG maintenance immunotherapy in patients with high-risk NMIBC [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary for patients with intermediate risk or poor-risk prognosis of metastatic kidney cancer, surgical therapy can often be deferred in favour of effective systemic therapy, which does not require hospital admissions 20. However, in any oncological disease, the diagnosis and timely treatment should not be compromised 19 22…”
Section: Discussionmentioning
confidence: 99%
“…The current COVID-19 pandemic underlines the importance of changing some aspects of urology practice, from patient consultation to the triage of urologic surgeries. The pandemic of COVID-19 has serious implications on urology practice and raises particular questions for urologists about the management of different conditions [36].…”
Section: Discussionmentioning
confidence: 99%